All Days 2012
DOI: 10.2118/154846-ms
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Deep Shale Gas Drilling: A Case Study in Sichuan Basin

Abstract: As an unconventional gas resource, shale gas has been developed mostly in shallow reservoirs which are mainly buried in depth form 76 m to 2439 m in the world. However, the deep shale gas is drawing more attention as time goes by. In this paper, deep shale gas in Sichuan Basin is studied as an example where the shale gas reservoirs are mostly buried deep in depth from 2300 m to 4500 m. Because the shale gas in Sichuan Basin is buried deep with high formation pressure and the formation conditions are complex, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The shale in Well YX1 is characterized by large thickness (nearly 40 m), high abundance of organic matter (average TOC of 5.8%), high-over maturity, presence of matrix pores (average porosity of 3.2%), and part of the fractures have a certain aperture, presenting favorable evidence for "geological sweet spots". Moreover, it is dominated by siliceous shale facies, with comparable elastic modulus, Poisson's ratio, and brittleness to other global shale gas reservoirs (Abousleiman et al, 2007;Sone and Zoback, 2010;Koesoemadinata et al, 2011;Kumar et al, 2012;Li et al, 2012;Wang R. Y. et al, 2016b), recording as good conditions for "engineering sweet spots". Therefore, the key factors for why the shale gas of Well YX1 cannot form industrial gas flow may be attributed to fault and fracture damage to the reservoir.…”
Section: Control Of Faults and Fractures On Shale Gasmentioning
confidence: 99%
“…The shale in Well YX1 is characterized by large thickness (nearly 40 m), high abundance of organic matter (average TOC of 5.8%), high-over maturity, presence of matrix pores (average porosity of 3.2%), and part of the fractures have a certain aperture, presenting favorable evidence for "geological sweet spots". Moreover, it is dominated by siliceous shale facies, with comparable elastic modulus, Poisson's ratio, and brittleness to other global shale gas reservoirs (Abousleiman et al, 2007;Sone and Zoback, 2010;Koesoemadinata et al, 2011;Kumar et al, 2012;Li et al, 2012;Wang R. Y. et al, 2016b), recording as good conditions for "engineering sweet spots". Therefore, the key factors for why the shale gas of Well YX1 cannot form industrial gas flow may be attributed to fault and fracture damage to the reservoir.…”
Section: Control Of Faults and Fractures On Shale Gasmentioning
confidence: 99%
“…Water, white oil and kerosene can invade into shale to a certain degree [13] along with bedding planes when exposed to the shale. White oil and kerosene are the main components of oil based drilling fluids used in shale gas reservoirs.…”
Section: Oil Invasion and Lubricationmentioning
confidence: 99%
“…Through several field case studies, they also demonstrated the importance of stick-slip considerations, some mitigation techniques, and issues related to several downhole heating failures resulting from excessive wellbore friction in the horizontal sections. Li et al (2012) described the challenges in deep shale gas drilling through a case study in the Sichuan basin where reservoirs are primarily buried deep, from approximately 7, 500 ft to 15, 000 ft. They discussed the issues related to wellbore instability, serious formation damage resulting from high drilling fluid pressure, and low drilling efficiency that is encountered while drilling in a high formation pressure basin and under complex formation conditions.…”
Section: Drilling Challenges In Shale Playsmentioning
confidence: 99%
“…White et al (1987) presented a casing wear estimation technique using laboratory measurements and performed field predictions; additional casing wear modeling methods are presented in literature by Kumar et al (2013) and Samuel et al (2014). While addressing challenges related to horizontal drilling applications, Samuel et al (2013) also documented all existing casing wear models together that provide an insight into the current problem.…”
Section: Pipe Body Wearmentioning
confidence: 99%